NILAI PENDIDIKAN DAN PERAN MASJID KI MAROGAN SEBAGAI SEJARAH KEBUDAYAAN ISLAM DI KOTA PALEMBANG - Hudaidah, Hudaidah; Swanto Yusni, Irfan; Sumantri, M. Danish; Aulan, Aulan; Ramadani, Indah (Jurnal Al-Fatih, 2025)
This article discusses the educational value and role of Ki Marogan Mosque in Palembang as a significant heritage of Islamic history and culture in South Sumatra. It was founded by a cleric named Masagus Haji Abdul Hamid bin Masagus Haji Mahmud or nicknamed Kiai Marogan in the late 19th century. This mosque not only functions as a place of worship, but also a center of education, social, cultural, and religious tourism destinations. This research uses a literature study that traces the educational value, historical journey, architectural development, and functions of the Ki Marogan Mosque from time to time. The architecture of this mosque shows the acculturation of local culture with Arabic, Indian and Chinese influences. In addition, Ki Marogan's tomb complex located in the mosque area is the main attraction in the community's spiritual pilgrimage. In the modern context, the mosque continues to adapt by utilizing digitalization for historical preservation and Islamic propagation. The results show that Ki Marogan Mosque not only acts as a religious symbol, but also as a center for preserving local values, history, and Palembang cultural identity.